2023
DOI: 10.2478/prilozi-2023-0022
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Polymorphism rs3918242 of the Matrix Metalloproteinase-9 Gene with Coronary Artery Disease in a Younger Population

Abstract: Coronary artery disease (CAD) is a complex disease resulting from the interaction of numerous so-called traditional risk factors and comorbid conditions on the one side (such as dyslipidemia, smoking, obesity, diabetes, hypertension) and genetic factors on the other. The evidence of a genetic contribution to the development of CAD, especially in the last 2 decades is consistent. It is important that a number of established gene polymorphisms in the younger CAD population are in the genes involved in the inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…The R279Q polymorphism had no direct effect on MMP-9 concentration but was associated with CV events in patients with stable angina [17]. Boshev et al studied the rs3918242 polymorphism in a younger population with CAD and concluded that this polymorphism could be used for clinical risk assessment for the development of CAD [34].…”
Section: Discussionmentioning
confidence: 99%
“…The R279Q polymorphism had no direct effect on MMP-9 concentration but was associated with CV events in patients with stable angina [17]. Boshev et al studied the rs3918242 polymorphism in a younger population with CAD and concluded that this polymorphism could be used for clinical risk assessment for the development of CAD [34].…”
Section: Discussionmentioning
confidence: 99%